Desenvolvimento motor, cognitivo e funcional de crianças nascidas pré-termo e a termo, de níveis sociais diferentes, aos quatro de idade - Eliane Fernandes Maggi (2012)
Objective: Compare both motor coordination and cognitive development and functional performance of preterm and term born children belonging to different social levels at the age of four. Methods: Cross-sectional and observational study of which 124 children enrolled (62 preterm and 62 term), aging from 4 years old to 4 years and 11 months old distributed in 4 distinct groups according to the gestational age, weight at birth and socioeconomic level. Group 1 consisted of 31 children born with a gestational age 34 weeks, birth weight 1500 g belonging to a low socioeconomic level. Group 2 consisted of 31 children born with a gestational age 34 weeks, birth weight 1500 g belonging to a high socioeconomic level. Group 3 consisted of 31 children born with a gestational age 37 weeks, birth weight 2500 g belonging to a low socioeconomic level. Group 4 consisted of 31 children with a gestational age 37 weeks, birth weight 2500 g belonging to a high socioeconomic level. All children were evaluated by the tests of Movement Assessment Battery for Children Second Edition (MABC-2), Pediatric Evaluation of Disability Inventory and Columbia Mental Maturity Scale. All normality variables were examined for The Shapiro-Wilk Normality test. For Groups comparison Mann-Whitney Test and T-Test were performed. In order to evaluate any association between the groups Chi-Square Test was used. The level of significance 0,05 was considered for all analyses. Results: Concerning motor development, 35.5% of the preterm children from low socioeconomic level (RNPT LS), 22.6% of the preterm from high socioeconomic level (RNPT HS) and 6.5% of the full term children, from either high (RNT HS) and low socioeconomic level (RNT LS) presented scores in MABC-2 indicative of developmental coordination disorder (DCD). In the Columbia, RNPT HS had better performance than RNPT LS and RNT NSA had better performance than RNPT HS, between RNPT LS and RNT HS there was no significant difference. In the PEDI, RNPT HS presented more limited repertoire of functional skills and required more assistance from the caregiver than the RNT HS; the RNPT LS showed more limited functional skills than the RNT LS, however, there was no significant difference in caregiver assistance; RNPT HS presented more limited functional skills´ repertoire than RNPT LS, with no difference in caregiver assistance. Conclusion: Outcomes reinforce evidences that preterm infants are more likely to present alterations in the development than their peers. Environmental factors, mainly socioeconomic levels seem to interfere in these infants development since preterm infants of high socioeconomic level performed tests better than preterm infants of low socioeconomic level.